Respostas
respondido por:
1
n.(n-1)!
----------
(n-1)!
Corta o (n-1)!
Resposta: n
----------
(n-1)!
Corta o (n-1)!
Resposta: n
respondido por:
1
Ola Wilian
n!/(n - 1)! = n*(n - 1)!/(n - 1)! = n
outra
x! (x+2)!/(x-1)(x+1) =
x!*(x + 2)*)x + 1)*x! /(x + 1)*(x - 1) =
(x!)²*(x + 2)/(x - 1)
.
n!/(n - 1)! = n*(n - 1)!/(n - 1)! = n
outra
x! (x+2)!/(x-1)(x+1) =
x!*(x + 2)*)x + 1)*x! /(x + 1)*(x - 1) =
(x!)²*(x + 2)/(x - 1)
.
logwillian:
muito obrigado pode me dizer como simplificar x! (x+2)!/(x-1)(x+1)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás